Gambaran Faktor-Faktor Yang Mempengaruhi Kelengkapan Imunisasi Dasar Pada Anak Di Masa Pandemi Covid-19 - Fakhrana Hanniyati; Ganis Indriati; Oswati Hasanah (HEALTH CARE : JURNAL KESEHATAN, 2022)
Every child should get immunization because immunization was an important thing, during pandemic that impact all around the world some Puskesmas were still giving health services but so many Puskesmas stop the immunization service. This research aims to identify a description of the factors that affect the completeness of basic immunization in children during the COVID-19 pandemic. This research using quantitative with descriptive and retrospective closure. The sample is 75 mothers that have 9-24 months old children that fullfill the criteria. This research using descriptive analysis. The result of this research is the availability of the health care facilities was in a good condition with 86.7%, health worker support was in giving a good support with 93.3%, and mother family support was giving a good support with 81.3%. 50 mother action on giving completeness of bacsic immunizations on children during Pandemic COVID-19 was on complete status with 66.7%. Completeness of basic immunization during pandemic COVID-19 was affecting by the availability of the health care facilities, support from health worker, support from family.